Descriptive Analysis of User Satisfaction with SIANIS Application Services in Higher Education Environments - Iis Sumandari; Tamrin Tamrin; Katriza Katriza (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
his study aims to comprehensively evaluate the level of user satisfaction with the Non-Inventory Expendable Asset Information System (SIANIS) implemented at the Faculty of Teacher Training and Education, Sriwijaya University by reviewing the quality of electronic services provided through the system. This study is motivated by the increasing importance of implementing a digital-based asset management system in supporting administrative efficiency, transparency, and accuracy of data management in higher education environments. The study uses a descriptive quantitative approach involving 50 respondents consisting of students and laboratory administrative staff who actively use the SIANIS application in academic and administrative activities. Data collection was carried out through the distribution of structured questionnaires using a five-point Likert scale, while data analysis was carried out using descriptive statistical techniques based on the e-Servqual framework which includes seven dimensions, namely efficiency, system availability, fulfillment, privacy, responsiveness, compensation, and contact. The results of the study indicate that the overall level of user satisfaction with the SIANIS application is in the